2020
DOI: 10.3390/ijms21134649
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Detection of Endogenous HIV Activation by Dynamic Nuclear Polarization NMR and Flow Cytometry

Abstract: We demonstrate for the first time in-cell dynamic nuclear polarization (DNP) in conjunction with flow cytometry sorting to address the cellular heterogeneity of in-cell samples. Utilizing a green fluorescent protein (GFP) reporter of HIV reactivation, we correlate increased 15N resonance intensity with cytokine-driven HIV reactivation in a human cell line model of HIV latency. As few as 10% GFP+ cells could be detected by DNP nuclear magnetic resonance (NMR). The inclusion of flow cytometric sorting of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…The most common cryoprotectant for cultured mammalian cells is dimethylsulfoxide (DMSO) at a concentration of 10% (v/v). Indeed, the handful of studies that examine preparations of mammalian cells using DNP NMR use DMSO ( Albert et al, 2018 ; Narasimhan et al, 2019 ; Schlagnitweit et al, 2019 ; Overall et al, 2020 ), although the sample composition—including the choice of cryoprotectant—and post-experiment cellular viability, have only very recently been considered ( Ghosh et al, 2020 ; Ghosh et al, 2021 ; Overall and Barnes, 2021 ). Given the widespread preference for 10% DMSO over 15% glycerol as the cryoprotectant for cellular cryopreservation, we sought to determine if cryoprotection using 10% DMSO could also support cellular viability throughout the DNP NMR experiments.…”
Section: Introductionmentioning
confidence: 99%
“…The most common cryoprotectant for cultured mammalian cells is dimethylsulfoxide (DMSO) at a concentration of 10% (v/v). Indeed, the handful of studies that examine preparations of mammalian cells using DNP NMR use DMSO ( Albert et al, 2018 ; Narasimhan et al, 2019 ; Schlagnitweit et al, 2019 ; Overall et al, 2020 ), although the sample composition—including the choice of cryoprotectant—and post-experiment cellular viability, have only very recently been considered ( Ghosh et al, 2020 ; Ghosh et al, 2021 ; Overall and Barnes, 2021 ). Given the widespread preference for 10% DMSO over 15% glycerol as the cryoprotectant for cellular cryopreservation, we sought to determine if cryoprotection using 10% DMSO could also support cellular viability throughout the DNP NMR experiments.…”
Section: Introductionmentioning
confidence: 99%
“…(20% DMSO with 20 mM AMUPol, 60/30/10 glycerol/D 2 O/H 2 O with 20 mM AMUPol or PBS with 20 mM AMUPol), to give a final AMUPol concentration of 10 mM ( Sauvee et al, 2013 ). The cells were then incubated for the indicated times before packing into 3.2 mm sapphire cylindrical rotors (Bruker Biospin) using custom made Teflon filling tools ( Overall et al, 2020 ) by centrifugation for 1 min at 1,500 rpm. Rotors were plunge frozen in liquid nitrogen for 10 min before capping with zirconia drive caps.…”
Section: Methodsmentioning
confidence: 99%
“…The first demonstration of in-cell DNP within intact mammalian cells showed that significant enhancements could be achieved in the context of intact cells with a range of polarizing agents ( Albert et al, 2019 ), with an added benefit that the DNP enhancement can be targeted to subcellular compartments. Subsequent studies used DNP-NMR to observe exogenously labelled ubiquitin electroporated into HeLa cells ( Narasimhan et al, 2019 ), drug mediated expression of HIV particles ( Overall et al, 2020 ) and antisense RNA drug complexes in HEK 293T cells ( Schlagnitweit et al, 2019 ). However, this potential remains largely untapped.…”
Section: Introductionmentioning
confidence: 99%
“…This area is the largest in terms of the number of related publications and includes 91 articles, namely [ 1 , 2 , 3 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 ,…”
Section: Articles On the Various Directionsmentioning
confidence: 99%